Italian craft beer revolution: do spatial factors matter?. Issue 3 (21st August 2017) - Esposti, Roberto; Fastigi, Matteo; Viganò, Elena
Abstract : Purpose: The purpose of this paper is to investigate the emergence of microbreweries in Italy over the last 20 years (period 1993-2014) and assess its main determinants. Design/methodology/approach: The recent intense growth is expressed by the increasing number of entries in the sector actually accompanied, in most recent years, by an increasing number of exits. The paper proposes a quantitative assessment of this entry-exit dynamics through a sequence of econometric models known as survival models. Findings: Together with two other orders of possible determinants (idiosyncratic characteristics and the exogenous evolution of the beer market), the paper assesses the role played by specific geographical and local factors within these dynamics. Estimation results show that, whereas market force and individual features unquestionably affect entry and exit choices, geographical and local factors are of limited relevance, especially for the recent entry dynamics. Originality/value: Although the literature on the so-called craft beer revolution is already vast and increasing, the novel contribution of the paper concerns the specificity (if any) of the Italian case and the role of spatial factors in this respect. This investigation is performed adopting an advanced quantitative approach and this attempt is also quite original within this literature.